Systems Biology The Challenge of Complexity - Nakanishi, Shigetada; Kageyama, Ryoichiro; Watanabe, Dai (Springer Japan : Imprint: Springer, 2009)
Biological signaling pathways dynamically interact with one another to form complex information networks intracellularly, intercellularly, and eventually at the level of the organism. Biology and medicine have conventionally focused on identification and characterization of functional elements in biological signaling pathways. Recently, research in this field has pursued a new approach, systems biology, to understand the dynamics, complexity, and physiological functions of the biological signaling networks. Instead of reductionistic analyses or large-scale studies of biomolecules piece by piece, systems biology emphasizes the need for interdisciplinary methods and analysis of the regulation and operation of information networks at the systems level. The contributors to this book are leading researchers in the rising field of systems biology. Readers will find not only the most recent advances in research, but also the latest information about interdisciplinary methods and related topics.